A TiO2 nanowire photocatalyst for dual-ion production in laser desorption/ionization (LDI) mass spectrometry - Kim, Moon-Ju; Park, Jong-Min; Yun, Tae Gyeong; Noh, Joo-Yoon; Kang, Min-Jung; Pyun, Jae-Chul (ROYAL SOC CHEMISTRY, 2020)
It has been challenging to detect small analytes in both positive and negative ion modes using organic matrices in conventional matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). Herein, TiO2 nanowires are presented as a solid matrix to form dual ions of analytes regardless of their chemical properties and to demonstrate versatile applicability in LDI-MS.
Keywords: SURFACE; MATRIX; NANOPARTICLES; DESORPTION; MECHANISM; SILICA